Molecular Imaging of Hydrolytic Enzymes Using PET and SPECT. (15th September 2017) - Rempel, Brian P.; Price, Eric W.; Phenix, Christopher P.
Hydrolytic enzymes are a large class of biological catalysts that play a vital role in a plethora of critical biochemical processes required to maintain human health. However, the expression and/or activity of these important enzymes can change in many different diseases and therefore represent exciting targets for the development of positron emission tomography (PET) and single-photon emission computed tomography (SPECT) radiotracers. This review focuses on recently reported radiolabeled substrates, reversible inhibitors, and irreversible inhibitors investigated as PET and SPECT tracers for imaging hydrolytic enzymes. By learning from the most successful examples of tracer development for hydrolytic enzymes, it appears that an early focus on careful enzyme kinetics and cell-based studies are key factors for identifying potentially useful new molecular imaging agents.